Magnesium air battery negative electrode material and preparation method thereof

Through the preparation process of magnesium blocks and germanium alloys, the problem of low discharge performance of magnesium air batteries is solved, and efficient energy conversion and low-cost production are achieved.

CN119433311APending Publication Date: 2025-02-14TAIYUAN UNIVERSITY OF TECHNOLOGY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411574336.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The actual discharge voltage and energy conversion efficiency of magnesium air batteries are low, mainly due to the adhesion effect of the anode material and the hysteresis anode reaction kinetics, as well as the anode hydrogen evolution and self-corrosion caused by the negative difference effect.

Method used

An alloy composed of magnesium blocks and germanium is prepared by melting, refining, double-stage solid solution treatment, extrusion treatment and annealing treatment under a protective atmosphere to prepare a magnesium air battery negative electrode material with excellent discharge performance.

Benefits of technology

The discharge voltage and energy conversion efficiency of magnesium air batteries are improved, the self-corrosion and block effect of hydrogen evolution are suppressed, the production cost is reduced, and the effect of refining grains is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433311A_ABST
    Figure CN119433311A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnesium-air battery electrode materials, and discloses a magnesium-air battery negative electrode material and a preparation method thereof, and the magnesium-air battery negative electrode material comprises the following components by mass: 99.9% of magnesium and 0.1% of germanium. The non-toxic and environment-friendly element germanium is added, and the total adding amount of the element germanium does not exceed 0.1%, so that the cost of the negative electrode material is reduced, the reaction kinetics of the positive electrode is improved, and no second phase is generated. The alloy composed of magnesium and germanium does not have a precipitated phase, has a uniform micron-sized equiaxed grain structure, has an average recrystallization grain size of 16.28 + / -0.29 [mu] m, and has good discharge performance and high dissolution kinetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium-air battery electrode materials, and in particular to a magnesium-air battery negative electrode material and a preparation method thereof. Background Art

[0002] Metal-air batteries have the characteristics of clean use, easy access to raw materials, high energy conversion efficiency, and high energy density, making them a new type of energy storage device with great development potential. Metal-air batteries mainly include lithium-air batteries, zinc-air batteries, magnesium-air batteries, etc. In contrast, magnesium-air batteries have attracted much attention due to their high theoretical discharge voltage, energy density, and relatively negative standard electrode potential. However, there are two major problems with the anode materials of magnesium-air batteries at present: on the one hand, the adhesion effect of the discharge product and the hysteresis of the anode reaction kinetics make the actual discharge voltage have a large gap with the theoretical discharge voltage. On the other hand, the negative difference effect (NDE) induces serious anode hydrogen evolution and self-corrosion, greatly reducing the energy conversion efficiency of the magnesium alloy anode. Therefore, the development of magnesium anode materials with high reaction activity, loose and easy-to-fall-off product films, and suppressed hydrogen evolution reaction and block effect is the key to improving the discharge performance of magnesium-air batteries.

[0003] Research has shown that alloying coupled with plastic deformation can effectively improve the discharge performance of the negative electrode. However, high alloying will increase production costs, and the introduction of second phase impurity particles will cause micro-galvanic corrosion, leading to severe local corrosion and reducing the performance of the negative electrode. Summary of the invention

[0004] In view of this, the present invention proposes a magnesium-air battery negative electrode material and a preparation method thereof, aiming to solve the problems of low actual discharge voltage and energy conversion efficiency of magnesium-air batteries in current technology.

[0005] The invention provides a magnesium-air battery negative electrode material, which comprises the following components in percentage by mass: magnesium: 99.9%, germanium: 0.1%.

[0006] The method for preparing the negative electrode material of the magnesium-air battery comprises the following steps:

[0007] (1) Under a protective atmosphere, a magnesium block and a germanium are melted to obtain an alloy liquid, a refining agent is added to the alloy liquid for refining, and after the refining is completed, casting and cooling are performed in sequence to obtain an ingot;

[0008] (2) Under a protective atmosphere, the ingot is subjected to a two-stage solid solution treatment to obtain a solid solution matrix;

[0009] (3) extruding the solid solution matrix to obtain an extruded rod;

[0010] (4) The extruded rod is annealed to obtain the negative electrode material of the air battery.

[0011] Furthermore, the protective atmosphere in step (1) is carbon dioxide and sulfur hexafluoride, and the volume ratio of carbon dioxide to sulfur hexafluoride is (35-45):1.

[0012] Furthermore, the melting temperature in step (1) is 710-750°C.

[0013] Furthermore, the refining agent in step (1) is a mixture of MgCl2, KCl, BaCl2 and CaF2, and the mass ratio of MgCl2, KCl, BaCl2 and CaF2 is 46:40:8:5;

[0014] The refining temperature is 740° C., and the refining time is 1-2 minutes.

[0015] Furthermore, the protective atmosphere in step (2) is argon.

[0016] Furthermore, the specific steps of the double-stage solution treatment in step (2) are: a first solution treatment and a second solution treatment performed sequentially;

[0017] The temperature of the first solution treatment is 310-330°C, and the holding time of the first solution treatment is 50-70min;

[0018] The temperature of the second solution treatment is 480-520° C., and the holding time of the second solution treatment is 170-190 min.

[0019] Furthermore, the annealing temperature in step (4) is 280-320° C., and the annealing holding time is 8-12 min.

[0020] The present invention also provides application of the magnesium-air battery negative electrode material in a magnesium-air battery.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention provides a magnesium-air battery negative electrode material, comprising the following components in mass percentage: magnesium: 99.9%, germanium: 0.1%. The invention adds non-toxic and environmentally friendly element germanium, the total addition amount of which does not exceed 0.1%, reduces the cost of the negative electrode material, improves the anode reaction kinetics, and does not produce a second phase.

[0023] The alloy composed of magnesium block and germanium has no precipitation phase and has a uniform micron-sized equiaxed grain structure with an average recrystallized grain size of 16.28±0.29μm.

[0024] The magnesium-air battery negative electrode material provided by the invention has good discharge performance and high dissolution kinetics.

[0025] The preparation method of the negative electrode material of a magnesium-air battery comprises the following steps: (1) melting a magnesium block and germanium under a protective atmosphere to obtain an alloy liquid, adding a refining agent to the alloy liquid for refining, and casting and cooling the ingot after the refining is completed; (2) performing a double-stage solid solution treatment on the ingot under a protective atmosphere to obtain a solid solution matrix; (3) performing an extrusion treatment on the solid solution matrix to obtain an extruded rod; (4) performing an annealing treatment on the extruded rod to obtain the negative electrode material of the air battery. The present invention uses magnesium blocks and germanium as raw materials, and prepares a magnesium-air battery negative electrode material with excellent discharge performance through melting, refining, double-stage solid solution treatment, extrusion treatment, and finally annealing. The preparation method has a simple process flow and is easy to operate.

[0026] The present invention adopts a process flow of direct extrusion after double-stage solid solution treatment, which shortens the preparation process, can achieve the effect of grain refinement after extrusion, and improves the comprehensive performance of the negative electrode material of the magnesium-air battery.

[0027] After extrusion treatment, the solid solution matrix obtains a uniform equiaxed fine-grained structure, which significantly improves the dissolution kinetics of the negative electrode, effectively inhibits hydrogen evolution self-corrosion and block effect, and improves the discharge performance.

[0028] When the magnesium-air battery negative electrode material provided by the present invention is used in a magnesium-air battery as a negative electrode, the discharge voltage is 1.44V and the anode utilization rate is 60.62%. -2 At this current density, the discharge voltage reaches 1.06V and the energy density reaches 1741.83mW·h·g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0030] Figure 1 This is a crystal phase organization diagram of the negative electrode material of the air battery obtained in Example 1 of the present invention;

[0031] Figure 2 This is a diagram showing the average grain size of the negative electrode material for an air battery obtained in Example 1 of the present invention;

[0032] Figure 3 This is a characterization test diagram of the air battery negative electrode material obtained in Example 1 of the present invention;

[0033] Where a is the SEM microstructure diagram, and b is the XRD diagram;

[0034] Figure 4 This is an electrochemical test diagram of the air battery negative electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0036] The invention provides a magnesium-air battery negative electrode material, comprising the following components in percentage by mass: magnesium: 99.9%, germanium: 0.1%.

[0037] In one embodiment, the purity of the magnesium is preferably >99.9%, and the purity of the germanium is preferably >99.9%.

[0038] The method for preparing the negative electrode material of the magnesium-air battery comprises the following steps:

[0039] (1) Under a protective atmosphere, a magnesium block and a germanium are melted to obtain an alloy liquid, a refining agent is added to the alloy liquid for refining, and after the refining is completed, casting and cooling are performed in sequence to obtain an ingot;

[0040] (2) Under a protective atmosphere, the ingot is subjected to a two-stage solid solution treatment to obtain a solid solution matrix;

[0041] (3) extruding the solid solution matrix to obtain an extruded rod;

[0042] (4) The extruded rod is annealed to obtain the negative electrode material of the air battery.

[0043] In one embodiment, the magnesium block and the germanium need to be dried before use. The drying temperature is preferably 180-220° C., more preferably 190-210° C., and more preferably 195-205° C. The drying holding time is preferably 100-140 min, more preferably 110-130 min, and more preferably 115-125 min.

[0044] In one embodiment, the sequence in step (1) is to raise the temperature of the resistance furnace to 400° C., put some magnesium blocks in the crucible, and introduce protective gas to form a protective atmosphere.

[0045] In one embodiment, the crucible needs to be pre-treated before use. The pre-treatment steps are: placing the crucible on a resistance furnace at a temperature of 300°C for 20 minutes, taking out the crucible after the insulation is completed, and evenly applying the coating on the surface of the crucible. The number of times of application is preferably 3 times, and the composition of the coating is preferably zinc oxide, water and sodium silicate. The mass volume ratio of zinc oxide, water and sodium silicate is preferably 22.5g:120mL:22.5g.

[0046] In one embodiment, the protective atmosphere in step (1) is preferably carbon dioxide and sulfur hexafluoride, and the volume ratio of carbon dioxide to sulfur hexafluoride is preferably (35-45):1, further preferably (37-43):1, and more preferably (39-41):1.

[0047] In one embodiment, after a protective gas is introduced to form a protective atmosphere, the temperature of the resistance furnace is adjusted to the melting temperature. After the magnesium block is melted to form a magnesium alloy liquid, a slag spoon is used to remove the oxide film on the surface of the magnesium alloy liquid, and then germanium is added to the magnesium alloy liquid, and the remaining magnesium block is pressed onto the germanium surface for melting.

[0048] In one embodiment, the mass of the remaining magnesium block is greater than the mass of germanium. The purpose of pressing the remaining magnesium block onto the surface of germanium is to press the germanium below the liquid surface of the magnesium alloy to promote full melting of germanium.

[0049] In one embodiment, the skimmer needs to be pre-treated before use. The pre-treatment step is: place the skimmer on a resistance furnace at a temperature of 300°C for 20 minutes, take out the skimmer after the insulation is completed, and evenly apply a coating on the surface of the skimmer. The number of times of application is preferably 3 times, and the composition of the coating is preferably zinc oxide, water and sodium silicate. The mass volume ratio of zinc oxide, water and sodium silicate is preferably 22.5g:120mL:22.5g.

[0050] In one embodiment, the melting temperature in step (1) is preferably 710-750°C, more preferably 720-740°C, and more preferably 725-735°C.

[0051] In one embodiment, after germanium is melted to obtain alloy liquid, the system temperature is adjusted to the refining temperature for refining.

[0052] In one embodiment, the refining agent in step (1) is a mixture of MgCl2, KCl, BaCl2 and CaF2, and the mass ratio of MgCl2, KCl, BaCl2 and CaF2 is 46:40:8:5;

[0053] The refining temperature is preferably 740° C., and the refining time is preferably 1-2 min, more preferably 1.2-1.8 min, and even more preferably 1.4-1.6 min.

[0054] In one embodiment, a stirring rod is used to stir the alloy liquid during the refining process.

[0055] In one embodiment, the stirring rod needs to be pre-treated before use. The pre-treatment steps are: place the stirring rod on a resistance furnace at a temperature of 300°C for 20 minutes, take out the stirring rod after the insulation is completed, and evenly apply the coating on the surface of the stirring rod. The number of times of application is preferably 3 times, and the composition of the coating is preferably zinc oxide, water and sodium silicate. The mass volume ratio of zinc oxide, water and sodium silicate is preferably 22.5g:120mL:22.5g.

[0056] In one embodiment, after refining is completed, the temperature is adjusted to the melting temperature for heat preservation, and after heat preservation is completed, the system temperature is adjusted to the temperature for slag removal treatment, and slag removal treatment is performed. The heat preservation time is preferably 15-25 minutes, more preferably 17-23 minutes, and more preferably 19-21 minutes; the temperature for slag removal treatment is preferably 700-720°C, more preferably 705-715°C, and more preferably 708-712°C.

[0057] In one embodiment, the tool for deslagging is a deslagging spoon, and the purpose of deslagging is to remove the oxide film on the surface of the alloy liquid.

[0058] In one embodiment, the skimmer needs to be pre-treated before use. The pre-treatment step is: place the skimmer on a resistance furnace at a temperature of 300°C for 20 minutes, take out the skimmer after the insulation is completed, and evenly apply a coating on the surface of the skimmer. The number of times of application is preferably 3 times, and the composition of the coating is preferably zinc oxide, water and sodium silicate. The mass volume ratio of zinc oxide, water and sodium silicate is preferably 22.5g:120mL:22.5g.

[0059] In one embodiment, after the slag removal treatment is completed, the alloy liquid is poured into a mold for casting to obtain a blank. The material of the mold is preferably copper, and the mold needs to be preheated before use, and the preheating temperature is preferably 200°C.

[0060] In one embodiment, the cooling method in step (1) is preferably air static cooling.

[0061] In one embodiment, the protective atmosphere in step (2) is preferably argon.

[0062] In one embodiment, the double-stage solution treatment in step (2) is performed in a heat treatment furnace of model OTF-1200X.

[0063] In one embodiment, the specific steps of the two-stage solution treatment in step (2) are preferably: a first solution treatment and a second solution treatment performed sequentially;

[0064] The temperature of the first solution treatment is preferably 310-330°C, more preferably 315-325°C, more preferably 317-323°C, and the holding time of the first solution treatment is preferably 50-70min, more preferably 55-65min, more preferably 58-62min;

[0065] The temperature of the second solution treatment is preferably 480-520°C, more preferably 490-510°C, more preferably 495-515°C, and the holding time of the second solution treatment is preferably 170-190min, more preferably 175-185min, more preferably 177-183min.

[0066] In one embodiment, after the double-stage solution treatment is completed, water quenching is performed to obtain a solid solution matrix.

[0067] In one embodiment, the solid solution matrix is ​​machined to form an extrusion blank, which is then subjected to an extrusion process to obtain an extruded rod. The extrusion process temperature is preferably 300° C., and the extrusion ratio is preferably 25:1.

[0068] In one embodiment, the annealing temperature in step (4) is preferably 280-320°C, more preferably 290-310°C, and more preferably 295-305°C. The annealing holding time is preferably 8-12 min, more preferably 9-11 min, and more preferably 9.5-10.5 min.

[0069] The present invention also provides application of the magnesium-air battery negative electrode material in a magnesium-air battery.

[0070] Example 1

[0071] The magnesium block and germanium particles were dried in an oven at 200°C for 2 h and set aside.

[0072] The crucible was placed on a resistance furnace at 300°C for 20 minutes. After the heat preservation was completed, the crucible was taken out and the coating was evenly applied on the surface of the crucible three times. The coating composition was zinc oxide, water and sodium silicate, wherein the mass volume ratio of zinc oxide, water and sodium silicate was 22.5g:120mL:22.5g.

[0073] Place the skimmer on a resistance furnace at 300°C for 20 minutes, take out the skimmer after the end of the heat preservation, and evenly apply the coating on the surface of the skimmer for 3 times. The coating is composed of zinc oxide, water and sodium silicate, wherein the mass volume ratio of zinc oxide, water and sodium silicate is 22.5g:120mL:22.5g.

[0074] The stirring rod was placed on a resistance furnace at 300°C for 20 minutes. After the temperature was maintained, the stirring rod was taken out and the coating was evenly applied on the surface of the stirring rod for 3 times. The coating was composed of zinc oxide, water and sodium silicate, wherein the mass volume ratio of zinc oxide, water and sodium silicate was 22.5g:120mL:22.5g.

[0075] The resistance furnace was heated to 400°C, 530 g of the pretreated magnesium block was placed in the pretreated crucible, and a mixed gas of carbon dioxide and sulfur hexafluoride (the volume ratio of carbon dioxide and sulfur hexafluoride was 40:1) was introduced to form a protective atmosphere. The temperature of the resistance furnace was adjusted to 710°C and kept warm for 25 minutes. The magnesium block was melted to form a magnesium alloy liquid. The oxide film on the surface of the magnesium alloy liquid was removed with a slag spoon, and then the pretreated germanium was added, and the remaining 69.4 g of the pretreated magnesium block was pressed onto the surface of the germanium. After the germanium and the magnesium block were melted to obtain the alloy liquid, the system temperature was cooled to 740°C, a refining agent (the mass ratio of MgCl2, KCl, BaCl2 and CaF2 was 46:40:8:5) was added, and the alloy liquid was stirred for 2 minutes with a stirring rod for refining. After the refining is completed, the temperature is adjusted to 740℃ and kept at 740℃ for 20 minutes. After the insulation is completed, the system temperature is adjusted to 710℃ for slag removal to remove the oxide film on the surface of the alloy liquid. After the slag removal is completed, the alloy liquid is poured into a preheated 200℃ copper mold for casting under the condition of a mixed gas of carbon dioxide and sulfur hexafluoride (the volume ratio of carbon dioxide and sulfur hexafluoride is 40:1) to obtain a billet. The billet is cooled in the air to obtain an ingot.

[0076] Under argon atmosphere, the ingot was placed in an OTF-1200X heat treatment furnace for a two-stage solution treatment, wherein the first-stage solution treatment was carried out at 320°C for 60 minutes, and the second-stage solution treatment was carried out at 500°C for 180 minutes. After the two-stage solution treatment was completed, water quenching was performed to obtain a solid solution matrix.

[0077] The solid solution matrix was machined to produce an extruded billet with a diameter of 50 mm and a height of 50 mm, and then hot extruded at 300° C. with an extrusion ratio of 25:1 to obtain an extruded rod.

[0078] The extruded rod was annealed at 300° C. for 10 min to obtain the negative electrode material for the air battery.

[0079] Performance Testing

[0080] The negative electrode material of the air battery obtained in Example 1 was placed under a microscope for observation. The specific crystal phase structure diagram is as follows Figure 1 As shown, from Figure 1 It can be seen that the air battery negative electrode material provided by the present invention has no precipitated phase and has a uniform micron-scale equiaxed grain structure.

[0081] The average grain size of the negative electrode material of the air battery obtained in Example 1 was tested, and the results were as follows: Figure 2 As shown, according to the Nanomeasure test software, the average grain size was tested to be 16.28±0.29μm.

[0082] The air battery negative electrode material obtained in Example 1 was characterized and tested. Figure 3 As shown. a is the SEM microstructure diagram, and b is the XRD diagram. Figure 3 It can be seen that the air battery negative electrode material provided by the present invention has only α-Mg single phase.

[0083] Electrochemical tests were performed using a typical three-electrode system electrochemical workstation of Wuhan Coster CS350H model, wherein the platinum sheet was the auxiliary electrode, the air battery negative electrode material prepared in Example 1 of the present invention was the working electrode, the saturated calomel electrode was the reference electrode, and the electrolyte was a 3.5wt% NaCl solution.

[0084] Electrochemical tests include open circuit potential test, dynamic potential polarization and impedance spectrum test. The test was carried out according to the following process. First, the open circuit potential test was carried out for 1 hour. After that, the impedance spectrum test was carried out with the frequency set to 100kHz-10mHz and the voltage set to 5mV. Finally, the dynamic potential polarization test was carried out with the scanning speed of 0.1mV / s and the scanning range of -2V to -1V. The specific results are as follows: Figure 4 As shown, from Figure 4 It can be seen that, combined with the CorShow software, the slope of the anode branch of the polarization curve is 52.08, the slope of the cathode branch of the polarization curve is 389.92, and the corrosion current density is 344.34μA / cm 2 .

[0085] Application Example 1

[0086] The air battery negative electrode material obtained in Example 1 is used as the negative electrode of the air magnesium battery.

[0087] Application Example 2

[0088] Pure magnesium is used as the negative electrode of the magnesium-air battery.

[0089] The performance of Application Example 1 was tested at different discharge current densities, and the results are shown in Table 1.

[0090] Table 1 Performance test results of Application Example 1 at different discharge current densities

[0091] <![CDATA[Discharge current density / mA·cm -2 > Discharge voltage / V Anode efficiency / % <![CDATA[Energy density / mW·h·g -1 > 0.5 1.4420 16.92 659.45 2.5 1.2725 38.91 1338.53 5 1.1880 48.90 1552.73 10 1.0631 60.62 1741.83

[0092] It can be seen from Table 1 that the energy density of the magnesium-air battery negative electrode material provided by the present invention increases with the increase of current density, and the peak value is 1741.83 mW·h·g -1 .

[0093] The batteries of Application Example 1 and Application Example 2 were tested at a discharge current density of 10 mA cm -2 The battery performance under these conditions is shown in Table 2.

[0094] Table 2 Application Example 1 and Application Example 2 at a discharge current density of 10 mA cm -2 Battery performance test results

[0095]

[0096] It can be seen from Table 2 that at 10 mA cm -2 The magnesium-air battery negative electrode material provided by the present invention exhibits better discharge voltage, anode efficiency and energy density than pure magnesium.

[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A magnesium-air battery negative electrode material, characterized in that: The composition comprises the following mass percentages: magnesium: 99.9%, germanium: 0.1%; The magnesium-air battery negative electrode material is prepared by the following method: (1) Under a protective atmosphere, magnesium blocks and germanium are melted to obtain a molten alloy, a refining agent is added to the molten alloy for refining, and after the refining is completed, casting and cooling are performed in sequence to obtain an ingot; (2) Under a protective atmosphere, the ingot is subjected to a two-stage solid solution treatment to obtain a solid solution matrix; (3) extruding the solid solution matrix to obtain an extruded rod; (4) The extruded rod is annealed to obtain the magnesium-air battery negative electrode material.

2. A magnesium-air battery negative electrode material as claimed in claim 1, characterized in that: The protective atmosphere in step (1) is carbon dioxide and sulfur hexafluoride, and the volume ratio of carbon dioxide to sulfur hexafluoride is (35-45):

1.

3. A magnesium-air battery negative electrode material as claimed in claim 2, characterized in that: The melting temperature in step (1) is 710-750°C.

4. A magnesium-air battery negative electrode material as claimed in claim 3, characterized in that: The refining agent in step (1) is a mixture of MgCl2, KCl, BaCl2 and CaF2, and the mass ratio of MgCl2, KCl, BaCl2 and CaF2 is 46:40:8:5; The refining temperature is 740° C., and the refining time is 1-2 minutes.

5. A magnesium-air battery negative electrode material as claimed in claim 4, characterized in that: The protective atmosphere in step (2) is argon.

6. A magnesium-air battery negative electrode material as claimed in claim 5, characterized in that: The specific steps of the double-stage solution treatment in step (2) are: a first solution treatment and a second solution treatment performed sequentially; The temperature of the first solution treatment is 310-330°C, and the holding time of the first solution treatment is 50-70min; The temperature of the second solution treatment is 480-520° C., and the holding time of the second solution treatment is 170-190 min.

7. A magnesium-air battery negative electrode material as claimed in claim 6, characterized in that: The annealing temperature in step (4) is 280-320° C., and the annealing holding time is 8-12 min.

8. Use of a magnesium-air battery negative electrode material according to any one of claims 1 to 7 in a magnesium-air battery.

Citation Information

Patent Citations

  • Microalloyed magnesium alloy negative electrode material as well as preparation method and application thereof

    CN118531271A

  • Magnesium-air battery negative electrode material Mg-Ga alloy and preparation method thereof

    CN118756020A

  • Improvements in making alloy extruded forms by powder metallurgy

    GB690783A